Clonal Propagation of Rhynchostylis retusa (Lin.) Blume through in vitro Culture and their Establishment in the Nursery (Plant Tissue Culture and Biotechnology, 2012)
For high frequency regeneration of Rhyncnostylis retusa (Lin.) Blume apical nodal segments were used. Half strength MS + 2% sucrose + 1.5 mg/l BA + 0.5 mg/l NAA + 2 g/l peptone + 10% (v/v) coconut water (CW) + 0.5 g/l activated charcoal (AC) was the best nutrient medium, on which 89% cultures induced 8 microshoots per culture. Subculture of microshoots for further 8 weeks on the same nutrient medium enhanced the number of microshoots up to 95. For further proliferation of microshoots, their development into shoots as well as formation of secondary microshoots from the base of the old ones, the best medium was half strength of MS + 2% sucrose + 2 g/l peptone + 10% (v/v) CW + 0.5 g/l AC + 150 mg/l L-glutamine. Plantlets with roots were obtained in half strength of  MS + 2% sucrose + 2 g/l peptone + 10% (v/v) CW + 0.5 g/l AC + 5.0  g/l banana powder, on which cent per cent shoots rooted within eight weeks. The pH of all the categories of cultures were maintained at 5.6 before adding 2.2 g/l gelrite and autoclaving, and the cultures were incubated at 2000 - 3000 lux for 16/8 hrs light/dark at 24 ± 2ºC. Regeneration of plantlets continued due to repeated subculture of microshoots and regenerants were acclimatized and established in the nursery. Plant Tissue Cult. & Biotech. 22(1): 1-11, 2012  (June) DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11242